A comprehensive photovoltaic study on tungsten disulfide (WS2) buffer layer based CdTe solar cell. Issue 3 (March 2023) - Emon, E.I.; Islam, A.M.; Sobayel, M.K.; Islam, S.; Akhtaruzzaman, Md; Amin, N.; Ahmed, A.; Rashid, M.J.
Abstract: Transition metal di-chalcogenides (TMCDs)-Tungsten disulfide (WS2 ) exhibit excellent optoelectronic properties such as suitable bandgap, high absorption coefficient, good conductivity, high carrier mobility, etc. to be used as a photovoltaic material for thin-film solar cells. In the present work, we have replaced the traditional buffer CdS and ITO/ZnO window layer in CdTe solar cells with the non-toxic, earth-abundant WS2 buffer and SnO2 window layer, respectively. The SCAPS-1D solar simulator is used to investigate the potentiality of WS2 as buffer material in CdTe solar cells. This numerical study provides a comparison of the performances between the proposed structure: SnO2 /WS2 /CdTe/Au and the baseline structure: ITO/ZnO/CdS/CdTe/Au. The impacts of the charge carrier generation rate, spectral response, current-voltage characteristics, bulk defect density, defect density at buffer/absorber interface, operating temperature, and capacitance-voltage characteristics on the solar cell performance parameters have also been analyzed. The tolerance level of defect density in WS2 bulk and WS2 /CdTe interface are found to be 10 17  cm −3 and 10 12  cm −3, respectively. The temperature study reveals the poor structural robustness and thermal stability of the proposed cell. The conversion efficiency of the proposed cell has found to be 20.55% at the optimized device structure. Nevertheles, these findings may provide an insight to fabricate viable, environment friendly, and inexpensive CdTe thin-film solar cells.